2019
DOI: 10.1111/1753-6405.12931
|View full text |Cite
|
Sign up to set email alerts
|

Public health job advertisements in Australia and New Zealand: a changing landscape

Abstract: Objective: To describe available public health jobs in Australia and New Zealand by comparing recent job advertisements. Methods: We screened vacancies from 14 online job boards for public health jobs in late 2018. Data collected included information on job titles, sector, contract tenure, location and salary. We compared our findings with those of a job advertisements study from 2005. Results: We found 333 public health job advertisements in Australia and New Zealand. Common roles included project officers, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Several research studies on PHW have utilized job descriptions analysis to discern employer demands. [37][38][39][40][41] New technologies and methodologies allow for ISCO-08 and SOC coding of large-scale job postings data, thereby creating a list of occupations for which employers are currently seeking PHGs. Utilizing job postings data, to contrast with existing taxonomies, also provides data-driven, 'real time' insights more quickly than periodic surveys or expert opinion.…”
Section: Utility Of Job Postings Analysis To Classify Phwmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies on PHW have utilized job descriptions analysis to discern employer demands. [37][38][39][40][41] New technologies and methodologies allow for ISCO-08 and SOC coding of large-scale job postings data, thereby creating a list of occupations for which employers are currently seeking PHGs. Utilizing job postings data, to contrast with existing taxonomies, also provides data-driven, 'real time' insights more quickly than periodic surveys or expert opinion.…”
Section: Utility Of Job Postings Analysis To Classify Phwmentioning
confidence: 99%
“…Although job postings are not created for the purposes of workforce research, many studies have been conducted which leverage the rich, text‐based information from job postings—approximately 85% of which are posted on the internet 36 —to infer employer needs and workforce trends. Several research studies on PHW have utilized job descriptions analysis to discern employer demands 37–41 …”
Section: Introductionmentioning
confidence: 99%
“…However, different courses have different labour markets, and it is not a given that public health courses (or any course in particular) should grow proportionally over time. A previous study of job demand for public health in Australia showed that demand had increased between 14% and 60% from 2003 to 2018 8 . This is far less than the growth of course completions in the same time frame, with growth in completions over this time being two‐ to three‐fold higher than the growth in job advertisements.…”
Section: Discussionmentioning
confidence: 92%
“…There are potential issues associated with the increased expansion of public health education, such as the delineation between undergraduate and postgraduate offerings and the relationship between courses offered and the job market. For example, recent Australian research examined job advertisements for public health jobs, 8 and while it showed that a public health qualification was the most commonly required qualification, very few employers specified which level of qualification (e.g. undergraduate or postgraduate) they considered essential.…”
mentioning
confidence: 99%
“…Houghton, Braunack-Mayer and Hiller interviewed graduates from Adelaide University’s Bachelor of Health Sciences from 1992 to 1999 [ 7 ], finding that whilst the majority (59%) worked in ‘public health’, they were ‘doing so in a wide range of roles, reflecting the diversity of the public health workforce’. In 2019, Watts et al found that public health job advertisements are distributed among government, not-for-profit, academia, and the private sector, whilst also having a great deal of occupational variance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%